A comparison of acceleration and maximum speed sprint training on eccentric hamstring strength and hamstring muscle architecture - Freeman, B.; James, L.; Opar, D.; Tapley, S.; Young, W. (Journal of Science and Medicine in Sport, 2021)
Background: Hamstring strain injuries (HSI) are prevalent in field sports with a high-speed running component. It is widely believed that sprint training can have a HSI preventative effect due to the relatively high muscle activation. However, it is not known whether acceleration or maximum speed training is more effective for influencing HSI risk indicators such as eccentric strength or fascicle length. Therefore, the purpose was to investigate the differences between acceleration and maximum speed sprint training on eccentric hamstring strength and BFLH architecture. Methods: Community footballers (age = 23.1 ± 3.8, n = 12) were recruited for six-weeks of acceleration or maximum speed sprint training. Athletes completed pre- and post-testing consisting of a 40-m sprint test with 0-10-m and 30-40-m splits, an eccentric hamstring assessment on the NordBord, and an ultrasound assessment of the BFLH. Athletes were ranked on eccentric hamstring strength then separated into three groups: acceleration (n = 4), maximum speed (n = 4) and control (n = 4). Sample size was limited due to COVID-19 restrictions. Acceleration and maximum speed training was completed twice weekly. Ultrasound assessment was performed 24-hours post-session 2, 4, 6, 8, 10 and, 12. Athletes were asked to rate their soreness on a Likert scale 24-hours post-session. Results: Mean eccentric hamstring strength improved in the acceleration (5.3%, d = 0.27) and maximum speed (3.5%, d = 0.31) groups, however, not in the control (0.9%, d = 0.09) group. Acceleration (+23%, d = 1.59) and maximum speed (+20%, d = 1.81) athletes increased BFLH fascicle length compared to control athletes (-6%, d = -0.31). Acceleration improved by 2% and 3% for the acceleration and maximum speed athletes respectively. Likewise, maximum speed improved by 11% and 8% for the acceleration and maximum speed athletes. Control athletes performed 2% worse in acceleration and 1.5% better in maximum speed. Neither intervention reported excessive soreness post-sessions. Discussion: These findings indicate that sprint training for the mitigation of HSI risk factors is a promising training intervention. Specifically, the large increase in BFLH fascicle length suggests that the inclusion of regular sprint training should contribute to a well-rounded strength and conditioning program. There appear to be no substantial differences between the two training interventions, however, both interventions outperformed control subjects who completed their normal training schedule during this period. Minimal hamstring muscle soreness, coupled with clear improvements in speed qualities suggest that sprint training acts as a performance enhancement and injury prevention method.